Pengaruh Model Pengajaran Langsung (Direct Instruction) Berbantuan Media Laboratorium Virtual Terhadap Penguasaan Konsep Fisika Peserta Didik - Ria Rizki Ekasari; Gunawan Gunawan; Hairunnisyah Sahidu; Ahmad Harjono (Indonesian Journal of Applied Science and Technology, 2022)
Conceptual mastery is a primary objective in physics education, as it serves as the foundation for students to understand natural phenomena and solve various scientific problems. However, observations at SMAN 1 Selong indicate that students' mastery of physics concepts remains low. One instructional alternative to address this issue is the Direct Instruction model supported by virtual laboratory media. This study aims to determine the effect of the Direct Instruction model supported by virtual laboratory media on students' mastery of physics concepts. This research employs an experimental method using a pretest-posttest control group design. The study population consisted of all Grade X students at SMAN 1 Selong; the sample was selected using purposive sampling, resulting in Class X MS 1 serving as the experimental group and Class X MS 5 as the control group. Data were collected using a conceptual mastery test administered before and after the intervention. The data were analyzed using normality tests, homogeneity tests, a two-tailed t-test, and the N-gain test. The results show that students in the experimental group achieved a greater improvement in conceptual mastery compared to those in the control group. Thus, it can be concluded that the implementation of the Direct Instruction model supported by virtual laboratory media has a positive effect on students' mastery of physics concepts and serves as an effective alternative for physics instruction.